2016
DOI: 10.1055/s-0042-105744
|View full text |Cite
|
Sign up to set email alerts
|

Persistent residual contamination in endoscope channels; a fluorescence epimicroscopy study

Abstract: Our observations suggest that wear effects in endoscope lumens may contribute to the adsorption of proteins, thus facilitating retention and survival of bacteria. As demonstrated by recent outbreaks worldwide despite recommended reprocessing, the development of antimicrobial-resistant bacterial strains, and the estimated prevalence of variant Creutzfeldt-Jakob disease (vCJD) in the UK particularly, combined with increasing demand for endoscopic procedures, call for sustained precautions and improved methods fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…(10,11) Endoscope disinfection failure may also be due to the gradual accumulation of organic soils and wear on the surfaces of endoscope channels resulting in reduced exposure of bacteria to biocide and subsequent biofilm formation on endoscope channels. (10,12,13) There are evidences that bacterial species can form biofilm in endsocope lumens. (10,14,15) Biofilm formation can also occur within an endoscope reprocessor due to faults in it, or inadequate preventative maintenance for the unit.…”
Section: Introductionmentioning
confidence: 99%
“…(10,11) Endoscope disinfection failure may also be due to the gradual accumulation of organic soils and wear on the surfaces of endoscope channels resulting in reduced exposure of bacteria to biocide and subsequent biofilm formation on endoscope channels. (10,12,13) There are evidences that bacterial species can form biofilm in endsocope lumens. (10,14,15) Biofilm formation can also occur within an endoscope reprocessor due to faults in it, or inadequate preventative maintenance for the unit.…”
Section: Introductionmentioning
confidence: 99%
“…Nine studies 183,[191][192][193][194][195][196][197][198] reported this outcome after autoclaving with and without other decontamination processes (Table 18): seven studies [192][193][194][195][196][197][198] for surgical instruments and two studies for endoscopes. 183,191 All studies were conducted in the UK. Seven studies 183,[193][194][195][196][197][198] reported on protein residue on instruments acquired between one and nine NHS trusts; the number of trusts involved was not reported in two studies.…”
Section: Clinical Evidencementioning
confidence: 99%
“…Seven studies 183,[193][194][195][196][197][198] reported on protein residue on instruments acquired between one and nine NHS trusts; the number of trusts involved was not reported in two studies. 191,192 All studies reported that cleaning essentially involved conventional procedures for the equipment concerned. With the exception of two studies, 192,193 the assay appears to have involved detection of protein in situ on the instruments.…”
Section: Clinical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…The recent outbreaks of bacterial infections involving reusable medical devices resulted in increased scrutiny of reprocessing protocols for such devices . Several research and clinical studies have assessed reprocessing related issues in reusable devices such as arthroscopic shavers, needleless injectors, biopsy forceps, suction tips, laryngoscopic blades, surgical instruments, anesthetic devices, and endoscopes . Preventing cross‐infection between patients is essential for reusable devices; therefore, the reprocessing protocol must ensure sufficient decontamination of the devices before reuse.…”
Section: Introductionmentioning
confidence: 99%